The benefit of Ramfjord teeth to represent the full-mouth clinical attachment level in epidemiological study - Omar H Ali; Hadeel Mazin (College of Dentistry/ University of Baghdad, 2014)
Background: Since the periodontal disease Index of Ramfjord (Ramfjord index) can potentially shorten the examination time by almost half, many studies evaluated Ramfjord teeth in predicting full-mouth periodontal status of an adult population. The aim of this study was to evaluate the benefit of Ramfjord teeth in predicting the full-mouth clinical attachment level of an adult population in patients attending the college of dentistry- Baghdad University. Materials and methods: The study participants were 100 patients with age range from 30-60 years old which represent group zero. The patients were divided into three main groups according to the age of the patients. Group I and group II each of them composed of 30 patients while group III composed of 40 patients. In the first time clinical attachment level (CAL) was measured from the full mouth (FM) and then from the Ramfjord teeth (RT) (teeth number: 16, 21, 24, 36, 41, 44) in all groups. Clinical attachment level (CAL) was measured in millimeters using periodontal probe. Results: The difference in the mean clinical attachment level measured from the full mouth (FM) and Ramfjord teeth (RT) by using paired t - test was non significant in all the groups. Also in all groups the correlation coefficient as well as beta coefficient was high. Conclusion: The high agreement between Ramfjord teeth and full mouth CAL confirm the epidemiological validity of Ramfjord teeth to represent the full mouth.